The automation of teaching processes based on knowledge processing - Svetsky, Stefan; Moravcik, Oliver (Transactions on Engineering and Computing Sciences, 2014)
Technology-enhanced learning as one of the EU research priorities is focused on "how information and communication technologies can be used to support learning and teaching". However, such “definition” is too much general, so, mostly technology-driven approaches are prevailing in the practice, which do not take enough in consideration didactic aspects of knowledge processing, and that teaching processes are related to mental processes of individuals. In addition, there are many open questions, especially “what is knowledge”, “what is knowledge representation”. An interdisciplinary definition of knowledge is missing, despite the fact that teaching processes are knowledge based. Within a long-term participatory action research on TEL when teaching bachelors, a strategy of automation of teaching processes was evolved. This seem to be a crucial point for solving any personalized computer support of teacher and students. Because these processes are primarily uncertain, or unstructured, it was found, that to make these processes better computerizable, an unification both teaching and informatics processes is needed. In this context, the knowledge processing is based on an idea of “virtual knowledge unit” (as a part of patent application, 2014). For this purpose, an in-house software has been developed that enables individuals to perform a “batch knowledge processing paradigm” in order to process a large amount of knowledge in natural language on their personal computers, university’s cloud and servers. This paper deals with a specific approach to automation of teaching processes based on the knowledge processing.